THE IMPACT OF READING ON IMPROVING SCHOOL LEADERSHIP - Aljabeli, Laila; Alqahtani, Abdulmuhsen (PEOPLE: International Journal of Social Sciences, 2017)
Reading is fundamental in developing the individual’s mind and creativity. Playing a vital role in conveying attitudes, ideas, and information, it is thought that the person’s overall performance is remarkably improved because of this habit. However, previous research has not adequately addressed the impact reading has on a school leader’s character. The objective of this paper is to bring to light this rarely tackled issue with special attention to the effect it has on a leader’s performance. Literature has shown that reading expands the leader’s knowledge, which in turn helps the administration’s progress. This paper suggests that providing a well-equipped library and encouraging educators to use it can play a key role in developing employees’ reading habits and can therefore benefit the institution. School principals can also conduct after school reading clubs to help principals from other schools throughout the country to share ideas and inspirations gained from reading.